2017
DOI: 10.7554/elife.23525
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Lifetime Imaging Microscopy reveals rerouting of SNARE trafficking driving dendritic cell activation

Abstract: SNARE proteins play a crucial role in intracellular trafficking by catalyzing membrane fusion, but assigning SNAREs to specific intracellular transport routes is challenging with current techniques. We developed a novel Förster resonance energy transfer-fluorescence lifetime imaging microscopy (FRET-FLIM)-based technique allowing visualization of real-time local interactions of fluorescently tagged SNARE proteins in live cells. We used FRET-FLIM to delineate the trafficking steps underlying the release of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(71 citation statements)
references
References 58 publications
2
69
0
Order By: Relevance
“…The lower estimate is assuming completely nonpolarized secretion, as suggested by a macrophage study where there was no evidence found for polarized secretion of IL‐6 in macrophages, whereas TNFα was predominantly secreted at the nascent cup of phagosomes . The higher estimate is for the case that IL‐6 is exclusively released at the ventral membrane, which we consider unlikely given that we recently showed the presence of VAMP3 in postfusion cis ‐SNARE complexes (i.e., the SNARE for IL‐6 release ) at the dorsal membrane. In the case where release of IL‐6 would be higher at the dorsal than the ventral membranes, we underestimate the rate of exocytic events and the average number of IL‐6 molecules per vesicle will be even lower.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…The lower estimate is assuming completely nonpolarized secretion, as suggested by a macrophage study where there was no evidence found for polarized secretion of IL‐6 in macrophages, whereas TNFα was predominantly secreted at the nascent cup of phagosomes . The higher estimate is for the case that IL‐6 is exclusively released at the ventral membrane, which we consider unlikely given that we recently showed the presence of VAMP3 in postfusion cis ‐SNARE complexes (i.e., the SNARE for IL‐6 release ) at the dorsal membrane. In the case where release of IL‐6 would be higher at the dorsal than the ventral membranes, we underestimate the rate of exocytic events and the average number of IL‐6 molecules per vesicle will be even lower.…”
Section: Discussionmentioning
confidence: 84%
“…C). This rate increased on average about twofold to ~ 0.0027 bursts·s −1 ·μm −2 upon overnight stimulation with LPS, likely due to the increased expression of trafficking proteins and the rerouting of intracellular trafficking . These are coarse estimates, with a 10‐fold variation among cells (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations